Physical, chemical, and microbiological evaluation of sausages produced with chicken meat affected by deep pectoral myopathy - Francelino, Mainara Carolina [UNESP]; Pereira, Mateus Roberto [UNESP]; Cavalcanti, Érika Nayara Freire [UNESP]; Dias, Ana Veronica Lino [UNESP]; Villegas-Cayllahua, Erick Alonso [UNESP]; Dutra, Daniel Rodrigues [UNESP]; Ferrari, Fábio Borba [UNESP]; Rodrigues, Romário Alves [UNESP]; de Souza, Rodrigo Alves [UNESP]; Giampietro-Ganeco, Aline [UNESP]; de Souza, Pedro Alves [UNESP]; de Oliveira, Rodrigo Fortunato; et al. (Elsevier, 2023)
The purpose of the present study was to characterize the chemical composition, lipid oxidation, and physical characteristics of fresh sausages produced with meat from the pectoralis major muscle affected by deep pectoral myopathy. For the characterization of myopathy, samples were collected from broiler chickens slaughtered between 42- and 46-days old in a slaughterhouse in the state of São Paulo. The experiment consisted of samples from pectoralis major muscle of birds affected or not by DPM (normal—absence of myopathy and DPM category 3—progressive degeneration of the pectoralis minor with a greenish appearance). After classification of the samples, a part of raw products with the pectoralis minor removed, was submitted to microbiological and physical analyses for the characterization of DPM. Afterward, only the pectoralis major muscle was used to manufacture fresh sausages and 2 groups were established. The evaluated parameters were: color, pH, water-holding capacity (WHC), cooking loss (CL), shear force (SF), water activity (Aw), and chemical composition. Meat pH was higher (P < 0.05) in meats with DPM, however, WHC values were lower (71.92%), which made CL value increase (25.31%). In addition, the coloring increased and the technological characteristics of raw breasts were less favorable with the presence of DPM. All fresh sausages’ color (except a* higher control group), pH, and Aw values were higher in DPM group. No effect on SF values was observed between fresh sausages. In chemical composition, only protein content increased in fresh sausages with DPM. Microbiological analyses did not indicate bacterial contamination of raw samples and fresh sausages. Data obtained in the present study suggest fresh sausages produced with breasts affected by DPM are a viable alternative and may confer more favorable qualitative characteristics to sausages than the raw marketed meat.
Keywords: broiler; meat quality; microbiology; sausage